The Influence Of Understanding, And The Firmness Of Tax Sanctions On The Reporting Of Individual SPT (Case Study At PT Abdi Harsa Karya) - Ardiansyah, Krisna; Yudiana, Yudiana; Mulyana Dali, Rahmat (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
This study aims to determine the partial and simultaneous effect on the variable Understanding and Firmness of Tax Sanctions on Reporting of SPT Individuals at PT Abdi Harsa Karya. This study used a quantitative method with a total sample population of 36 in the company PT Abdi Harsa Karya. The sampling technique used is purposive sampling technique . Purposive sampling is a sampling technique with certain considerations that an appropriate sample size in a study is 30-100 samples. This study uses multiple linear analysis using SPSS as a data processor. The results of the study show that understanding of taxation has no significant effect on taxpayer compliance and tax sanctions have a significant effect on taxpayer compliance. Understanding and tax sanctions have a significant influence on taxpayer compliance in SPT reporting.